THE INFLUENCE OF SUSTAINABLE CONSUMER TRENDS ON MODERN SME MARKETING STRATEGIES - Miftahul Jannah (Journal Informatic, Education and Management (JIEM), 2026)
The shift in consumer orientation toward sustainability principles has become one of the main determinants shaping changes in global business dynamics, including in the Micro, Small, and Medium Enterprises (MSMEs) sector. This research aims to comprehensively examine how changes in consumer preferences for environmentally-oriented products influence MSME marketing strategies in a contemporary business context. The approach used is a systematic literature review by examining 20 selected scientific publications published between 2020 and 2024. The literature reviewed covers the development of ideas on green marketing , consumer behavior , and sustainability management that are relevant to the formulation of sustainable business strategies.